Optimalitasi Digital Marketing pada UMKM Amadonathi melalui Sosial Media dan Website - Pratama, Abraham Yoga; Pambudi, Zefanya Albert; Magrita, Christeyssa; Sakti, Imanuel Madea (Adi Widya : Jurnal Pengabdian Masyarakat, 2023)
The online presence of MSMEs on various digital platforms is now a necessity. Two of them are social media and websites as digital marketing media. However, many MSMEs have limited understanding and capabilities regarding digital marketing. This community service activity occurred at UMKM Amadonathi, a donut culinary business in Salatiga City. These activities include training and assistance in designing content plans using Google Spreadsheets, creating content design using Canva, and developing websites using Google Sites. In addition, this activity was carried out pre-test and post-test to see the results before and after the training and mentoring activities. The results show an increase in the understanding of business actors about digital marketing. It is hoped that the results of activities in content plan, content design, and website can be continued and developed by Amadonathi’s business actors independently in the future.